The Effect of Implementing Differentiated Learning on Motivation to Learn Economics: Student Perceptions - Saputri, Anggun Bella; Joyoatmojo, Soetarno; Noviani, Leny (Economic Education Analysis Journal, 2024)
This study investigates the impact of employing differentiated learning and utilizing media on the learning motivation of students in Economics classes at SMA Negeri 7 Surakarta. It employs a quantitative survey approach with a population of 359 students from classes X-A to X-J. The sampling method involves proportional random sampling of 190 students, determined through the Slovin formula. Data collection utilizes a questionnaire, while data analysis employs binary logistic regression with SPSS as the analysis tool. The findings reveal that (1) Differentiated learning significantly and positively influences learning motivation, as indicated by a significance value of 0.000 < 0.05. This is attributed to the fact that, in differentiated learning, teachers are obligated to tailor instruction to individual students based on their readiness, interests, and learning profile; (2) Media use also significantly and positively influences learning motivation, with a significance value of 0.000 < 0.05. This is because incorporating media aids students in comprehending learning materials and mitigates boredom. This research contributes novel insights to the field of education, particularly in the context of differentiated learning. Consequently, future researchers may broaden the scope of their investigations by exploring teacher and student perspectives and incorporating additional relevant variables.